1996
DOI: 10.1172/jci118648
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus mapping of human blood pressure to a genetic region at or near the lipoprotein lipase gene locus on chromosome 8p22.

Abstract: Resistance to insulin-mediated glucose disposal is a common finding in patients with non-insulin-dependent diabetes mellitus (NIDDM), as well as in nondiabetic individuals with hypertension. In an effort to identify the generic loci responsible for variations in blood pressure in individuals at increased risk of insulin resistance, we studied the distribution of blood pressure in 48 Taiwanese families with NIDDM and conducted quantitative sib-pair linkage analysis with candidate loci for insulin resistance, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 46 publications
7
60
3
Order By: Relevance
“…They also failed to find any suggestive linkage between a-adducin gene and EH or the gene-gene interactions. In our study, D4S412 and D4S3038, 15 In the present study, however, the results cannot be replicated in an extended sample size of 108 Shanghai EH families. We also failed to find a linkage between the other four gene loci (OB, OBR, ADRB3 and LPL) and EH, although some significant linkage was reported in other populations (Table 4).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…They also failed to find any suggestive linkage between a-adducin gene and EH or the gene-gene interactions. In our study, D4S412 and D4S3038, 15 In the present study, however, the results cannot be replicated in an extended sample size of 108 Shanghai EH families. We also failed to find a linkage between the other four gene loci (OB, OBR, ADRB3 and LPL) and EH, although some significant linkage was reported in other populations (Table 4).…”
Section: Discussioncontrasting
confidence: 80%
“…Although the products of these five EH candidate genes act in the field of sodium balance or neuro-endocrine modulation, their actual roles in the pathogenesis of EH remain unknown. [14][15][16][17][18][19] Especially for the two genes OBR and ARBR3, no linkage study has been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect difficulties in the replication of supportive findings under complex circumstances modulating hypertension, such as the heterogeneous nature of genetic susceptibility and gene-environment interactions. 6 The affected sib-pair method has revealed that angiotensinogen, lipoprotein lipase and ␣-adducin gene polymorphisms are genetic risk factors for human essential hypertension, [7][8][9] but no specific gene clearly governing susceptibility for hypertension has yet been identified. The low-density lipoprotein (LDL) receptor is one candidate that plays an integral role in plasma lipoprotein metabolism.…”
Section: Journal Of Human Hypertension (2001) 15 125-130mentioning
confidence: 99%
“…Marker LPL1GTR2, located in the 5Ј region of the LPL gene, is described in detail in Odelberg and White. 23 D8S282 is 3 cM from the LPL gene and is described in Wu et al 24 Polymerase chain reactions for the markers were carried out by use of standard techniques and under standard conditions optimized for each marker. Exact concentrations and conditions are available on request from the authors.…”
Section: Genotypingmentioning
confidence: 99%